Mentoring the teaching-learning activity of gymnastics with video feedback to reduce the risk of injury: A cultural-historical activity theory contribution - Ciavaldini-Cartaut, Solange (Revue internationale du CRIRES / CRI_SAS international Journal)

(untitled) (Centre de recherche et d’intervention sur la réussite scolaire, 2022)
This study focuses on preservice teacher's mentoring in a French University Graduate Schools of Teacher Education. It focuses on physical education and learning activities of middle school pupils. Photographs and videos are mobilised during post-lesson mentoring conference to help the preservice teacher (PT) to reduce the risk of injury. The data from a case study are made up of extracts from mentoring interview and self-confrontation interview analysed from a cultural-historical activity theory perspective (C.H.A.T).  Results highlights the potential relevance of using 1)   traces of learning activity during mentoring interactions to optimise the pedagogical design of PT’s 2) and to prevent the risks of pupils’ physical integrity. The theoretical model contributes to a global understanding of the problems arising in the collective teaching-learning activity and about modalities contributing to the joint tutoring activity independently of the disciplinary field.